一个新的指标, 中国人内脏脂肪指数与中国社区成年人(特别是高血压或高血糖人群)尿白蛋白‐肌酐比值密切相关:来自REACTION研究的结果 - Binqi Li; Weiqing Wang; Zhengnan Gao; Xulei Tang; Li Yan; Qin Wan; Zuojie Luo; Guijun Qin; Lulu Chen; Guang Ning; Yiming Mu (Journal of Diabetes, 2022)
Abstract Background The association between the Chinese Visceral Adiposity Index (CVAI) and urinary albumin to creatinine ratio (UACR) has not been illustrated. The current study aimed to investigate the association between CVAI and UACR and to compare the discriminative power of CVAI, triglyceride, body mass index (BMI), waist circumference (WC), and waist‐to‐hip ratio (WHR) with UACR in the Chinese community population. Methods This study included 34 732 participants from the REACTION (Risk Evaluation of cAncers in Chinese diabeTic Individuals) study. Binary logistic regression analyses were performed to detect the association between CVAI, triglyceride, BMI, WC, WHR and UACR. Results Binary logistic regression analysis showed that, after adjusting for potential confounders, in women, CVAI (odds ratio [OR]:1.16, 95% confidence interval [CI]: 1.01–1.34) and triglyceride (OR: 1.18, 95% CI: 1.04–1.33) were associated with UACR, whereas BMI, WC, and WHR were not associated with UACR; in men, CVAI (OR: 1.24, 95% CI: 1.02–1.50), WC (OR: 1.21, 95% CI 1.00–1.48), and triglycerides (OR: 1.18, 95% CI 0.97–1.44) were associated with UACR, whereas BMI and WHR were not associated with UACR. Stratified analysis showed that the correlation between CVAI and UACR was stronger in the population with 5.6 ≤ fasting blood glucose (FBG) <7.0 or 7.8 ≤ post‐load blood glucose (PBG) <11.1 mmol/L, FBG ≥7.0 or PBG ≥11.1, systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg. Conclusions In the Chinese general population, CVAI and UACR were significantly associated in both genders. At higher CVAI levels, the population with prediabetes, diabetes, and hypertension has a more significant association between CVAI and UACR.